Hepatotoxicity of anti-tuberculosis therapy and the hepatoprotective effect of traditional medicine - Damini C.; Anuj Nautiyal; Bharat Joshi; Vishu Kumar; Dev Singh Jangpangi; Subhash Chandra; Samir Bhargava; Bhavna Kumar; Henrique D.M. Coutinho; Gorika Tomar (Food and Humanity, 2026)

Transcriptional landscape of coding-noncoding RNA interactions in gallstone-associated and de-novo gallbladder carcinoma - Nabanita Roy; Anupam Sarma; Avdhesh Kumar Rai; Prangan Nath; Gaurav Das; Subhash Khanna; Cinmoyee Baruah; Dhruba Kumar Bhattacharyya; Pankaj Barah (Functional & Integrative Genomics, 2026)

Understanding the brown planthopper (Nilaparvata lugens Stål) resistance in rice through biological and biochemical responses - Darshana Brahma; S. Rajna; Subhash Chander; C.N. Rajarushi; Ranjith Kumar Ellur; Jessa Joseph (Crop Protection, 2026)

Introgression of leaf rust resistance gene LrSel.212 derived from a wheat-rye recombinant line “Selection 212” into a popular wheat variety HD2932 - Subhash Bijarania; Vrinda Batra; Naman Raj; Hemant Sharma; Hariom Shukla; Ramesh Bhurta; Priyanka Agarwal; Niharika Mallick; M.G. Mallikarjuna; M. Niranjana; Shailendra Kumar Jha (Physiological and Molecular Plant Pathology, 2026)

Structure–function relationships of plant-derived antioxidants in ghee: oxidative stability, thermal behaviour, and simulated intestinal digestion - Aditya Kumar Jain; Tanmay Hazra; Ankit Bihola; Kunal Kumar Ahuja; Rohit Sindhav; Subhash Prasad; Manish Parmar (Food Chemistry, 2026)

Microplastic Contamination in Aquatic Biota: a Comparative Study of Fish Species from the Ganga and Gomti Rivers - Priyanshu Kumar; Kamla Pat Raw; Vertika Shukla; Ritu Singh; Sunita Mishra; Monica Sharma; Subhash Kumar Yadav; Narendra Kumar (Water, Air, & Soil Pollution, 2026)

Rabies: a brief note on diagnostics and prophylactics - Farha Deeba; Jaipal Meena; Dinesh Kumar; Harit Kasana; Subhash Chand; Shikha Yadav (VirusDisease, 2026)

Identification and Characterisation of Super Susceptible Bread Wheat (Triticum aestivum L.) Landraces against Leaf Rust Pathogen (Puccinia triticina Eriks.) - Naman Raj; Ujjwal Kapoor; Ramesh Bhurta; Vrinda Batra; Subhash Bijarania; Niharika Mallick; M. G. Mallikarjuna; Vaibhav Kumar Singh; Atul Kumar; Om Prakash Gangwar; Pramod Prasad; Subhash Chander Bhardwaj; et al. (Indian Journal of Genetics and Plant Breeding, 2026)

Retraction notice to “Rice straw derived graphene-silica based nanocomposite and its application in improved co-fermentative microbial enzyme production and functional stability” [Sci. Total Environ. 876 (2023) 162765] - Mohammed Asiri; Neha Srivastava; Rajeev Singh; Amer Al Ali; Subhash C. Tripathi; Abdulaziz Alqahtani; Mohd Saeed; Manish Srivastava; Ashutosh Kumar Rai; Vijai Kumar Gupta (Science of The Total Environment, 2026)

Hydrobiological drivers of zooplankton community structure and seasonal succession in a hypersaline endorheic ecosystem - Pankaj Yadav; Kanchan Singhvi; Dinesh Kumar Saini; Anima Sharma; Subhash Chandra (Wetlands Ecology and Management, 2026)

Pine Needle Biochar–Supported Ag/TiO₂/Mg(OH)₂ Nanocomposites for Photocatalysis and Biomedical Remediation - Subhash Chand; Ravi Kumar; Sheikh Showkat Ahmad; Satwinderjeet Kaur; Naveen Thakur; Kuldeep Kumar (Water, Air, & Soil Pollution, 2026)

Uttarkashi-strain based goatpox vaccine provides inadequate protection against lumpy skin disease in cattle - Ram Kumar; Deepak Kumar Sharma; Shweta Dhanda; Assim Verma; Subhash Kachhawaha; Rajesh Singathia; Sitaram Gupta; Abhishek Gaurav; Manisha Mathur; Dinesh Jain; T. Riyesh; Naveen Kumar; et al. (Veterinary Research Communications, 2026)

Optimizing Sugarcane Yield Through Seasonal Planting Strategies: A Field Study in Sub-Tropical Conditions - Priyanka Singh; Subhash Chandra Singh; Prasoon Kumar; Manmohan Singh (Sugar Tech, 2026)

Synergistic Effect of Potentilla nepalensis with Antibiotics: Targeting Bacterial Efflux Pumps Through Pharmacological, and Computational Approaches - Subhash Sharma; Vikas Kumar; Chirag N. Patel; Anuradha Sourirajan; Kamal Dev (Indian Journal of Microbiology, 2026)

Trend Analysis and Forecast of Arrivals and Prices of Mosambi Crop in Himachal Pradesh - Vishal Thakur; Anju Sharma; Rakesh Kumar Gupta; Ashu Chandel; Subhash Sharma; Sahil Verma; Vijit Gupta; Ridhi Chauhan (Applied Fruit Science, 2026)

A Robust Hybrid Deep Learning Model for GHI Forecasting Incorporating EEMD, CSA Optimization, and Transformer–GRU Networks - Girijapati Sharma; Subhash Chandra; Arvind Kumar Yadav (Pure and Applied Geophysics, 2026)

Bioefficacy of plant growth promoting rhizobacteria (PGPR) in the sustainable management of root-knot nematodes in eggplant - Megha Sharma; Sunita Devi; Sumit Vashisth; Dharmendra Kumar; Subhash Chand; Kumari Manorma; Rakesh Kumar; Parmod Verma; Balbir Singh Dilta; Abhay (Physiological and Molecular Plant Pathology, 2026)

Microbial-mediated phosphorus management under zero-tillage enhances maize productivity, P-use efficiency, and carbon management in a maize-wheat system - Amit Kumar; U.K. Behera; Shivadhar; Subhash Babu; Raghavendra Singh; Saurav Saha; Anil K. Choudhary; Adarsh Kumar; Gaurendra Gupta; B.A. Gudade; Anup Das; Vijay Singh Meena; et al. (Field Crops Research, 2026)

A new estimation strategy for the population mean under stratified double sampling: an empirical study based on production and productivity data - Mukesh Kumar Verma; Rahul Varshney; Subhash Kumar Yadav; Sarthak Sachdeva (Stochastic Environmental Research and Risk Assessment, 2026)

Application of machine learning tools for prediction of seed cotton yield in upland cotton (G. hirsutum L.) under irrigated ecosystem - Debashis Paul; Vinita Gotmare; M. Saravanan; Sandeep Bagri; Harish Kumbhalkar; Subhash Chandra; S. K. Verma; Rishi Kumar; Y. G. Prasad (Euphytica, 2026)

Analyzing Global Threat of Lumpy Skin Disease Virus Infection: A Comparative Study of a Time Series Model and Machine Learning Models Across 10 High-Risk Countries - Saif Ali Khan; Subhash Kumar Yadav; Yusuf Akhter (Current Microbiology, 2026)

Mitigating the Environmental Impacts of the Sugarcane Industry in India: A Review of Best Management Practices - Shreya Kotnala; Arunima Nayak; Brij Bhushan; Shalini Tiwari; Ajay Kumar; Mohd Amin Mir; Subhash Chandra (Sugar Tech, 2026)

Elwendia persica (Boiss.) Pimenov & Kljuykov from Indian Western Himalaya: impact of geographical locations on essential oil yield, chemical diversity, anti-bacterial, anti-diabetic and anti-oxidant activities - Gaurav Aggarwal; Anmol; Subhash Kumar; Vivesh Sood; Dharam Singh; Amit Chawla; Mohit Sharma; Upendra Sharma (Natural Product Research, 2026)

On the significance of solute transport-based entropy generation in emerging desalination technologies - Milana M. Mavinkurve; Aparna Anilkumar; Subhash Kumar; Yagnaseni Roy (Desalination, 2026)

Interactive Effects of Elevated CO2, Temperature, and Weed Competition on Mungbean - Dasari Sreekanth; Deepak Vishwanath Pawar; Rajeev Kumar; Shobha Sondhia; P. K. Singh; J. S. Mishra; Ankita Sinha; Subhash Chander; Nagaraju Mukkamula; B. Kiran Kumar (Agricultural Research, 2026)

Canopy orientation influences sunburn fruit temperature and peel anatomy in Kinnow and Daisy mandarins - Subhash Chander; Khushdeep Singh; Krishan Kumar (Vegetos, 2026)

An investigation of the effects of Static Coulomb stress variations of four thrust earthquakes on subsequent events - Ankush Kumar Ruhela; Josodhir Das; Subhash Chandra Gupta; Ram Bichar Singh Yadav (Arabian Journal of Geosciences, 2026)

Multi-model machine learning for predicting tractor operator discomfort caused by whole-body vibration - Amandeep Singh; Naser Nawayseh; Philippe Doyon-Poulin; Stephan Milosavljevic; Subhash Rakheja; Yash Kumar; Krishna N Dewangan; Catherine Trask; Siby Samuel (Computers and Electronics in Agriculture, 2026)

Kaolin and salicylic acid mitigate sunburn and enhance stress-responsive biochemical and fruit quality traits in Daisy Mandarin (Citrus reticulata Blanco) under arid conditions - Khushdeep Singh; Subhash Chander; Shalini Jhanji; Krishan Kumar; Gurteg Singh (Journal of Plant Biochemistry and Biotechnology, 2026)

Weed Management in Fodder Maize Using Herbicides Under Diverse Agro-Climates of India - R. K. Agrawal; Jeetendra Kumar Soni; S. K. Jha; R. V. Kale; Rajesh Kumar; Birendra Kumar; Usha C. Thomas; Subhash Chand; A. K. Roy; A. K. Jha; V. K. Yadav (International Journal of Plant Production, 2026)

Virulence analysis and geographical distribution of Puccinia striiformis f. sp. tritici pathotypes in North Western plains zone of India (2019–2021) - Muhammad Rafi Bawari; Ajit Singh; Rajender Singh Beniwal; Keshav Saharan; Om Prakash Gangwar; Pramod Prasad; Subodh Kumar; Subhash Chander Bhardwaj (Indian Phytopathology, 2026)

Augmenting Seed Potato Production Through Integration of Aeroponics, Apical Rooted Cuttings and Sprout Cutting Techniques: A Comprehensive Review - Murlidhar J. Sadawarti; S. P. Singh; Tanuja Buckseth; Vinod Kumar; Rajesh K. Singh; Ashwani K. Sharma; Subhash Katare; Pooja Jatav; Deepanshi Deora; Priyadarshani Khambalkar; R. K. Samadhiya; Brajesh singh (Agricultural Research, 2026)

Multifunctional assessment of Ag–metal oxide nanocomposites anchored on pine needle-derived activated carbon: Cytotoxicity, antimicrobial, and photocatalytic properties - Subhash Chand; Ravi Kumar; Sheikh Showkat Ahmad; Satwinderjeet Kaur; Naveen Thakur; Kuldeep Kumar (Journal of Environmental Chemical Engineering, 2025)

Effect of salinity stress on growth, physio-biochemical and ion homeostasis and activation of antioxidant defense responses in Avena spp. - Shahid Ahmed; Parichita Priyadarshini; I. Indu; Maneet Rana; Gajender Yadav; A. K. Rai; Subhash Chand; Monika Yadav; Mahendra Singh; Rajesh Kumar Singhal (Cereal Research Communications, 2025)

Comprehensive polyphenolic profiling, antioxidant, antimicrobial, and cytotoxicity studies of Rhynchostylis retusa (L.) Blume: a medicinal orchid - Anjna Kumari; Rishabh Kaundal; Smita Kapoor; Subhash Kumar; Dharam Singh; Yogesh Kumar Walia; Dinesh Kumar (Natural Product Research, 2025)

Assessment of Factors Influencing Farmers’ Choices of Marketing Channels for Kiwifruit (Actinidia deliciosa A. Chev.): Insights from the Indian Himalayan Region - Shilpa Sharma; Rakesh Kumar Gupta; Ashu Chandel; Vishal Singh Rana; Subhash Sharma; Neeraj Sankhyan; Umesh Sharma (Environment, Development and Sustainability, 2025)

Bovine β-defensin 129 (BBD129) polymorphisms associated with differential posttranslational O-glycosylation and phosphorylation modifications perturb the sperm functions and their fertilizing potential - Subhash Solanki; Abhishek Kumar; Poonam Kashyap; Rakesh Kumar; Tirtha Kumar Datta (Animal Reproduction Science, 2025)

Nutrient Dynamics and Partitioning for Sustaining Sugarcane Productivity Through Integrated Use of Biochar, Solid Digestate, Ash with Variable Dose of Fertilizers, Under Trans Indo-Gangetic Plain - Sanjay Singh Rathore; Kapila Shekhawat; Subhash Babu; Mona Nagargade; Rajiv Kumar Singh; Pravin Kumar Upadhyay; Vishal Tyagi; Anjali Patel (Sugar Tech, 2025)

Traditional and Machine Learning Models for Forecasting Apple Production and Cultivation Area - Saif Ali Khan; Dinesh K. Sharma; Alok Kumar Shukla; Med Ram Verma; Anju Sharma; Subhash Kumar Yadav (Applied Fruit Science, 2025)

Sustainable synthesis and multifunctional applications of biowaste-derived carbon nanomaterials and metal oxide composites: A review - Subhash Chand; Ravi Kumar; Naveen Thakur; Kuldeep Kumar; Ahmad Umar; Tubia Almas; Sotirios Baskoutas (Chemosphere, 2025)

In Vivo Seed Potato Production Possibilities Through Sprouts - Tanuja Buckseth; M. J. Sadawarti; Pooja Jatav; Rajesh K. Singh; Jagesh K. Tiwari; Vinod Kumar; Ashwani K. Sharma; Subhash Katare; S. P. Singh; Brajesh Singh (Potato Research, 2025)

Soil Carbon and Nutrient Cycling Regulated by Fine Roots Distribution and Dynamics in Teak (Tectona grandis L.)-Based Agroforestry System in Semi-Arid Central India - Asha Ram; Shubham Choure; Inder Dev; Naresh Kumar; Deepak Singh; Dhiraj Kumar; Sovan Debnath; S. Suresh Ramanan; Ashutosh Dwivedi; Raju Kumar; Sanjana Maurya; Subhash Babu; et al. (Journal of Soil Science and Plant Nutrition, 2025)

Enhancing solar radiation forecasting accuracy with a hybrid SA-Bi-LSTM-Bi-GRU model - Girijapati Sharma; Subhash Chandra; Arvind Kumar Yadav; Rahul Gupta (Earth Science Informatics, 2025)

Graphene oxide liquid crystal membranes offer precise molecular sieving - Sk Safikul Islam; Anjali Kumari; Shabnam Pathan; Ria Sen Gupta; P. Rajasekhar Reddy; S. Arya; Subhash Kumar; Yagnaseni Roy; K. Anki Reddy; Suryasarathi Bose (Chemical Engineering Journal, 2025)

Characterization of dual porosity in bioturbated tight sandstone reservoir: insight from Mesozoic Jhuran Formation of Kachchh–Saurashtra offshore basin—India - G. D. D. Jyotsna; Ajendra Singh; Subhash Kushwaha; Rajnish Kumar; Lavanya Puppala; Bhawanisingh G. Desai (Acta Geophysica, 2025)

Ultra-fast photocatalytic degradation of nitrophenols using catalytically Ag/Cr-doped ZnO nanoparticles isolated using Murraya koenigii and Rhododendron arboreum extracts - Tanuj; Rajesh Kumar; Santosh Kumar; Neerja Kalra; Subhash Sharma (Next Research, 2025)

Exergy-energy, economic and environmental evaluation of a solid oxide fuel cell based trigeneration system using double effect vapor absorption refrigeration system - Yunis Khan; Pawan Kumar Singh; Aftab Anjum; K.K. Sivakumar; Shikha Gupta; Subhash Mishra (International Journal of Refrigeration, 2025)

Comparative Study on Key Time Series Models for Exploring the Agricultural Price Volatility in Potato Prices - S. Vishnu Shankar; Ashu Chandel; Rakesh Kumar Gupta; Subhash Sharma; Hukam Chand; A. Aravinthkumar; S. Ananthakrishnan (Potato Research, 2025)

Antibacterial Activity, Phytochemical Analysis of C. coggygria Leaf Extracts Against S. typhi, and Computational Studies to Screen Potential Drug Candidates - Ankit Negi; Pooja Pant; Shalini Mathpal; Disha Tewari; Santosh Kumar Upadhyay; Subhash Chandra; Rishendra Kumar (Indian Journal of Microbiology, 2025)

Quantitative Analysis on Expression of Insecticidal Crystal Proteins in Different Plant Parts of BG-II Cotton Hybrids at Various Phenological Stages - Debashis Paul; Rishi Kumar; G. Balasubhramani; Sandeep Bagri; Subhash Chandra; S. Manickam; Satpal Singh; A. H. Prakash; Y. G. Prasad (Agricultural Research, 2025)

Investigating the possibility of using waste plastic fuel and gasoline fuel mixture in gasoline direct injection engine through experimental studies and the Taguchi method - Sumit Kanchan; Abhishek Mukhija; Subhash Sharma; Rohitash Choudhary; Rajesh Choudhary; Ravinder Kumar (Fuel, 2025)

The SAP-1 payload: A technology demonstration for space-based microbiology experiments - A. Lokaveer; Vikram Khaire; Thomas Anjana; Maliyekkal Yasir; S. Yogahariharan; Akash Dewangan; Saurabh Kishor Mahajan; Sakshi Aravind Tembhurne; Gunja Subhash Gupta; Devashish Bhalla; Anantha Datta Dhruva; Aloke Kumar; et al. (Advances in Space Research, 2025)

Evaluating the multiple benefits of constructed wetlands in the restoration of rural village ponds in the tropics - Kalzang Chhoden; Jhalesh Kumar; Rajesh Singh; Omkar Singh; V.C. Goyal; Subhash Vyas; Nihal Singh; Anne Dobel; Elliot Hurst; Laurence Carvalho; Vinay Kumar Tyagi (Journal of Water Process Engineering, 2025)

Correction: Performance Evaluation of INSAT‑3D Derived Outgoing Long Wave Radiation Over India Using Remotely Sensed Observations - Anoop Kumar Mishra; Chander Singh Tomar; Gajendra Kumar; Ashim K. Mitra; Subhash Chander Bhan (Journal of the Indian Society of Remote Sensing, 2025)

Salt Stress Tolerance and Calcium Signalling Components: Where We Stand and How Far We can Go? - Diksha Bisht; Shefali Mishra; Subhash C. Bihani; Tanashvi Seth; Ashish Kumar Srivastava; Girdhar K. Pandey (Journal of Plant Growth Regulation, 2025)

Investigating the aging-modulatory mechanism of Rasayana Churna, an Ayurvedic herbal formulation, using a computational approach - Amisha Bisht; Anita Nayal; Disha Tewari; Sanjay Kumar; Subhash Chandra (Biogerontology, 2025)

Sustainable nitrogen management in maize using optical sensor: Assessing yield, economics, and environmental impact - Pravin Kumar Upadhyay; Vinod Kumar Singh; Kapila Shekhawat; Brahma Swaroop Dwivedi; Rajendra Prasad Mishra; Rajiv Kumar Singh; Sanjay Singh Rathore; Susheel Kumar Singh; Meenu Rani; Sayantika Sarkar; Abir Dey; Subhash Babu; et al. (Field Crops Research, 2025)

Black rice bioactive with multifunctional health promotional activities: A special reference to wound healing activity with polyhydroxybutyrate composite - Subhash Kumar; Gwanjo Lee; Vishal Kumar; Gajanan A. Bodkhe; Youngsook Oh; Gitima Deka; Pil-Hoon Park; Myunghee Kim (Food Chemistry, 2025)

Predicting the potential distribution of three invasive insect pests (Tuta absoluta, Aleurodicus rugioperculatus and Phenacoccus manihoti) under future climate scenarios in India based on CMIP6 projections - Guru-Pirasanna-Pandi Govindharaj; Sujithra M; Subhash Kumar Sahu; Swagatika Sahoo; Sushmita Banra; Jaipal Singh Choudhary (Theoretical and Applied Climatology, 2025)

Pink Bollworm, Pectinophora gossypiella (Saunders) Infestation Escalates from Incipient to Serious Proportions in North Cotton Zone of India - Rishi Kumar; Debashis Paul; S. K. Sain; Amarpreet Singh; Subhash Chandra; Satpal Singh; Rupinder Singh Cheema; Y. G. Prasad (Journal of Crop Health, 2025)

Influence of Bemisia tabaci-Induced Plant Volatiles on the Host-Choice Behavior of Tuta absoluta - Subhash Shivaramu; Kamala Jayanthi Pagadala Damodaram; Anuj Bhatnagar; Kailash Chandra Naga; Varun Yennurukadirenahalli Byregowda; Aarti Bairwa; Sanjeev Sharma; Rajesh Kumar Singh; Brajesh Singh; Vivek Kempraj (Journal of Chemical Ecology, 2025)

Flupyradifurone application: A promising approach to curtail tomato leaf curl New Delhi virus (ToLCNDV) transmission vectored by Bemisia tabaci in potato farming - Nitish Modgill; Kailash Chandra Naga; Dnyaneshwar Madhukar Firake; Rahul Kumar Tiwari; Subhash Shivaramu; Ravinder Kumar; Anuj Bhatnagar; Tanuja Buckseth; Aarti Bairwa; Chandan Maharana; Sanjeev Sharma; Brajesh Singh (Crop Protection, 2025)

Performance Evaluation of INSAT-3D Derived Outgoing Long Wave Radiation Over India Using Remotely Sensed Observations - Anoop Kumar Mishra; Chander Singh Tomar; Gajendra Kumar; Ashim K. Mitra; Subhash Chander Bhan (Journal of the Indian Society of Remote Sensing, 2025)

Estimation of source parameters of local earthquakes near Koldam, Himachal Himalaya, India - Ankush Kumar Ruhela; Subhash Chandra Gupta; Josodhir Das (Arabian Journal of Geosciences, 2025)

Underutilized edible Himalayan herb, Viola canescens Wall.; chemical composition, antioxidant and antimicrobial activity against respiratory tract pathogens - Rishabh Kaundal; Subhash Kumar; Dharam Singh; Dinesh Kumar (Food Bioscience, 2024)

Combating micro/nano plastic pollution with bioplastic: Sustainable food packaging, challenges, and future perspectives - Subhash Kumar; Namo Dubey; Vishal Kumar; Inho Choi; Junhyun Jeon; Myunghee Kim (Environmental Pollution, 2024)

Identification and functional characterization of the npc-2-like domain containing rust effector protein that suppresses cell death in plants - Rajdeep Jaswal; Himanshu Dubey; Kanti Kiran; Hukam Rawal; Gulshan Kumar; Sivasubramanian Rajarammohan; Rupesh Deshmukh; Humira Sonah; Pramod Prasad; Subhash C Bhardwaj; Naveen Gupta; Tilak Raj Sharma (Molecular Biology Reports, 2024)

Impact of Different Tillage and Residue Retention Practices on Soil Nutrients, Microbial Community Composition and Grain Yield of Malt Barley - Om Parkash Ahlawat; Anil Khippal; Karnam Venkatesh; Rajender Singh Chhokar; Subhash Chander Gill; Prem Lal Kashyap; Ajit Singh Kharub; Lokendra Kumar; Neeraj Kumar; Anu Sharma; Kamini Kumari; Sonia Sheoran; et al. (Journal of Soil Science and Plant Nutrition, 2024)

Correction: Agro-Economic Assessment of Mechanized Rice Establishment Practices in Northwestern India: A Comparative Study - Ramkishor Kurmi; Satish Devram Lande; Indra Mani; Pramod Kumar Sahoo; Prolay Bhowmick; Niveta Jain; Rajeev Kumar; Chandu Singh; Mrinmoy Ray; Subhash Babu (International Journal of Plant Production, 2024)

Agro-Economic Assessment of Mechanized Rice Establishment Practices in Northwestern India: A Comparative Study - Ramkishor Kurmi; Satish Devram Lande; Indra Mani; Pramod Kumar Sahoo; Prolay Bhowmick; Niveta Jain; Rajeev Kumar; Chandu Singh; Mrinmoy Ray; Subhash Babu (International Journal of Plant Production, 2024)

Insights into Stable Apple Genotypes for Fruit Yield in Himachal Pradesh: An Assessment Using Parametric and Non-parametric Stability Measures - Neha Mishra; Rakesh Kumar Gupta; Ashu Chandel; Subhash Sharma; Pramod Verma; Hukum Chand Sharma; Geeta Verma; Samriti; Diksha Rana; Neha Sharma; Chinglembi Laishram; Tanvi Rajput; et al. (Applied Fruit Science, 2024)

Rapid transfer of the leaf rust resistance gene Lr52 for the improvement of bread wheat cultivar HD3086 - Naman Raj; Hariom Shukla; Priyanka Agarwal; Ajay Kumar Chandra; Ramesh Bhurta; Subhash Bijarania; Manish Kumar Choudhary; Raghunandan K; Niharika Mallick; Niranjana M; Arun Kumar M. B; Lekshmy Sathee; et al. (Physiological and Molecular Plant Pathology, 2024)

Crop establishment and nutrient management options: Optimizing productivity, maximize profitability and mitigating adverse climatic conditions in the maize-based production system of Northwest India - Mohammad Hasanain; V.K. Singh; S.S. Rathore; Vijay Singh Meena; Sunita Kumari Meena; Kapila Shekhawat; R.K. Singh; B.S. Dwivedi; Raghavendra Singh; Subhash Babu; P.K. Upadhyay; Amit Kumar; et al. (Field Crops Research, 2024)

Functional Genomics of Salt and Drought Stress Tolerance in the Temperate Crop Apple (Malus domestica) - Swati Verma; Namo Dubey; Vishnu Mishra; Subhash Kumar; Rajnish Sharma; Sneh Sharma; Ananda Kumar Sarkar; Ajay Kumar Thakur (Journal of Plant Growth Regulation, 2024)

Soil carbon sequestration potential of different land use systems: evidence from sub-humid southern plains and Aravalli hills of Rajasthan, India - Ram Bhawan Meena; Subhash Chander Meena; Avinash Chandra Rathore; Dinesh Chand Meena; Roshan Lal Meena; Nurnabi Meherul Alam; Kamal Kishor Sharma; Prabhat Kumar; Gopal Lal Meena; Murli Dhar Meena (Environmental Monitoring and Assessment, 2024)

Network pharmacology-based approach to investigate the molecular targets and molecular mechanisms of Rosmarinus officinalis L. for treating aging-related disorders - Amisha Bisht; Disha Tewari; Sanjay Kumar; Subhash Chandra (Biogerontology, 2024)

Geoheritage Values of Ambaji Region, Gujarat: Western India - Gaurav Chauhan; Sakshi V. Samji; Aditya Joshi; Manoj Limaye; J. M. Patel; Hemashri Thacker; Yash Shah; Bhavyata Chavada; Suraj Bhosale; Abhishek Lakhote; Chirag Jani; Suruchi Chauhan; et al. (Geoheritage, 2024)

Integrated organic nutrient management: a sustainable approach for cleaner maize (Zea mays L.) production in the Indian Himalayas - Amit Kumar; Raghavendra Singh; Subhash Babu; R. K. Avasthe; Anup Das; Aastika Pandey; B. A. Gudade; Ramgopal Devadas; Saurav Saha; Sanjay Singh Rathore (Organic Agriculture, 2024)

Cropping System Intensification: Implications on Food Security and Environmental Sustainability in India - Devideen Yadav; Subhash Babu; Dinesh Kumar Yadav; Anita Kumawat; Deepak Singh; Ajay Kumar Yadav; Sanjay Singh Rathore; Raghavendra Singh; Neeshu Joshi; Rajendra Kumar Yadav; Anup Das (Anthropocene Science, 2024)

Identification of hub genes associated with stripe rust disease in wheat through integrative transcriptome and gene-based association study - Divya Chauhan; Dwijesh Chandra Mishra; Shikha Mittal; Sushma Rani; Jyotika Bhati; Sundeep Kumar; Subhash C. Bhardwaj; Monendra Grover; Neeraj Budhlakoti; Suphiya Khan (South African Journal of Botany, 2024)

Co-fermentation of acid treated coconut wastes using mixed Bacillus cultures for enhanced production of extracellular enzymes: Application in bioconversion of raw coconut fibers - Manikant Tripathi; Neha Srivastava; Subhash C. Tripathi; Rajeev Singh; Irfan Ahmad; Ashutosh Kumar Rai; Noha E. Abdel-razik; P.K. Mishra; V Kumar Gupta (Food and Bioproducts Processing, 2024)

Unraveling the enigma of root-knot nematodes: from origins to advanced management strategies in agriculture - Sumit Vashisth; Pankaj Kumar; Vishav Gaurav Singh Chandel; Rakesh Kumar; Subhash Chander Verma; Rajeshwar Singh Chandel (Planta, 2024)

Correction to: On the Changes in Precipitation Spectrum Over India Using High-Resolution Precipitation Estimates from Remote Sensing Observations - Anoop Kumar Mishra; Ashim K. Mitra; Subhash Chander Bhan (Journal of the Indian Society of Remote Sensing, 2024)

Pyroxasulfone based tank-mix herbicide combinations for diverse weed flora control in wheat - Shiv Ram Samota; Rajender Singh Chhokar; Dharam Bir Yadav; Nitesh Kumar; Subhash Chander Gill; Harohalli Masthigowda Mamrutha (Crop Protection, 2024)

Network pharmacology, molecular docking, and molecular dynamics simulation to elucidate the mechanism of anti-aging action of Tinospora cordifolia - Amisha Bisht; Disha Tewari; Sanjay Kumar; Subhash Chandra (Molecular Diversity, 2024)

Morphotaxonomic and phylogenetic analysis of Saprolegnia aenigmatica from Arunachal Pradesh, India - Paras Nath Singh; Kadambari Subhash Pawar; Sanjay Kumar Singh; R. Singh; Gautam Datta (Indian Phytopathology, 2024)

Bacterial communities and their predicted function change with the life stages of invasive C-strain Spodoptera frugiperda (J. E. Smith, 1797) (Lepidoptera: Noctuidae) - Sushmita Banra; Jaipal Singh Choudhary; Anand Kumar Thakur; Anita Kumari; Priti Kumari Oraon; Naiyar Naaz; Subhash Kumar Sahu; Kanika Kumari (Biological Invasions, 2024)

Feeding potential and foraging behaviour of cheilomenes sexmaculata (F.) on cotton whitefly, Bemisia tabaci (Gennadius) - Rakesh Kumar; Sachin S. Suroshe; Y. Venkanna; M. C. Keerthi; Anoop Kumar; Subhash Chander (International Journal of Tropical Insect Science, 2024)

A comprehensive review on the phytochemistry, pharmacological properties, and in vitro propagation of an endemic medicinal orchid, Dactylorhiza hatagirea - Subhash Sharma; Vikas Kumar; Chandrika Attri Seth; Anuradha Sourirajan; Mohamed El-Shazly; Kamal Dev (Naunyn-Schmiedeberg's Archives of Pharmacology, 2024)

Drone remote sensing of wheat N using hyperspectral sensor and machine learning - Rabi N. Sahoo; R. G. Rejith; Shalini Gakhar; Rajeev Ranjan; Mahesh C. Meena; Abir Dey; Joydeep Mukherjee; Rajkumar Dhakar; Abhishek Meena; Anchal Daas; Subhash Babu; Pravin K. Upadhyay; et al. (Precision Agriculture, 2024)

Efficient Water Management Tactics for Mitigating Fruit Crop Diseases - Pradeep Kumar Vishwakarma; Subhash Chander; P. K. Nimbolkar (Applied Fruit Science, 2024)

Zinc oxide and ferric oxide nanoparticles combination increase plant growth, yield, and quality of soybean under semiarid region - Achchhelal Yadav; Subhash Babu; P. Krishnan; Baljeet Kaur; R.S. Bana; Debashis Chakraborty; Vikas Kumar; Bhawna Joshi; S.K. Lal (Chemosphere, 2024)

miR397b-LAC2 module regulates cadmium stress response by coordinating root lignification and copper homeostasis in Arabidopsis thaliana - Subhash Reddy Gaddam; Ashish Sharma; Prabodh Kumar Trivedi (Journal of Hazardous Materials, 2024)

Enhancing Wheat Productivity Through Genotypes and Growth Regulators Application Under Higher Fertility Conditions in Sub-humid Climate - Rajender Singh Chhokar; Neeraj Kumar; Subhash Chander Gill; Subhash Chandra Tripathi; Gyanendra Singh (International Journal of Plant Production, 2024)

Defoliator attack (Diorhabda lusca maulik) on Kharik (Celtis australis L.): effect on nutritive value, phenology and biomass productivity - Vaishali Sharma; D. R. Bhardwaj; Dhirender Kumar; Prashant Sharma; Subhash Chander Verma; Rohit Bishist (Agroforestry Systems, 2024)

Biochemical characterization of genome derived L-asparaginase from eurypsychrophilic Iodobacter sp. PCH194 for therapeutic and food applications - Virender Kumar; Sanyukta Darnal; Vijeta Patial; Subhash Kumar; Vikas Thakur; Vijay Kumar; Dharam Singh (Biologia, 2024)

On the Changes in Precipitation Spectrum Over India Using High-Resolution Precipitation Estimates from Remote Sensing Observations - Anoop Kumar Mishra; Ashim K. Mitra; Subhash Chander Bhan (Journal of the Indian Society of Remote Sensing, 2024)

Correction to: Giant proliferative spindle cell neoplasm of scalp - Anand Kumar Das; Suraj Kant Mani; Saraj Kumar Singh; Subhash Kumar (Acta Neurologica Belgica, 2024)

Giant proliferative spindle cell neoplasm of scalp - Anand Kumar Das; Suraj Kant Mani; Saraj Kumar Singh; Subhash Kumar (Acta Neurologica Belgica, 2024)

Entropy generation and exergy loss of R123-MWCNTs nanorefrigerant in flow condensation - Ravinder Kumar; Dwesh K Singh; Subhash Chander (International Journal of Refrigeration, 2024)

Sr65: a widely effective gene for stem rust resistance in wheat - Michael Norman; Chunhong Chen; Hanif Miah; Mehran Patpour; Chris Sørensen; Mogens Hovmøller; Kerrie Forrest; Subodh Kumar; Pramod Prasad; Om Prakash Gangwar; Subhash Bhardwaj; Harbans Bariana; et al. (Theoretical and Applied Genetics, 2024)

Modeling Global Monkeypox Infection Spread Data: A Comparative Study of Time Series Regression and Machine Learning Models - Vishwajeet Singh; Saif Ali Khan; Subhash Kumar Yadav; Yusuf Akhter (Current Microbiology, 2024)

Sustaining Rice-Wheat System Through Integrated Nutrient Management via FYM or Sesbania Aculeata in India on Long Term Basis - Subhash Chander; S C. Tripathi; Karnam Venkatesh; R. P. Meena; Neeraj Kumar; R. S. Chhokar; Nitesh Kumar; Shiv Ram Samota; Deepa Sharma; Gyanendra Singh (International Journal of Plant Production, 2023)

Identification of a resource-efficient integrated crop management practice for the rice-wheat rotations in south Asian Indo-Gangetic Plains - Niraj Biswakarma; Vijay Pooniya; R.R. Zhiipao; Dinesh Kumar; Y.S. Shivay; T.K. Das; Debasish Roy; Bappa Das; A.K. Choudhary; K. Swarnalakshmi; Prabhu Govindasamy; K.K. Lakhena; et al. (Agriculture, Ecosystems & Environment, 2023)

Spatial distribution and optimum sample size for monitoring of water lily aphid Rhopalosiphum nymphaeae (L.) in Makhana Euryale ferox Salisb - Vinod K. Padala; N Ramya; Manoj Kumar; S Rajna; Mandla Rajashekhar; YN Venkatesh; SM Raut; Subhash Chander; IS Singh; Mohd. Monobrullah (International Journal of Tropical Insect Science, 2023)

Experimental study on flow condensation pressure drop of R123-MWCNTs nanorefrigerant - Ravinder Kumar; Dwesh K Singh; Subhash Chander (International Journal of Refrigeration, 2023)

Buffalo sperm membrane glycan-binding proteins reveal precise and preferential binding signatures with specific glycans targets on oviduct epithelium and zona pellucida-an implication in fertilization - Poonam Kashyap; Subhash Solanki; Tirtha Kumar Datta; Rakesh Kumar (Theriogenology, 2023)

Purification of Industrial Effluent by Gas Hydrate-based (HyPurif) Process - Subhash Kumar Sharma; Anshu Bhadauria; T Nanda Kumar; Rajnish Kumar (Journal of Cleaner Production, 2023)

Analyses of Sequence Features and Expression Patterns of DOF Transcription Factor Genes in Pearl Millet (Pennisetum glaucum (L.) R. Br.) - Yingwei Qu; Shashi Kumar Gupta; Ambika Dudhate; Harshraj Subhash Shinde; Shenkui Liu; Tetsuo Takano; Daisuke Tsugama (Tropical Plant Biology, 2023)
Pearl millet ( Pennisetum glaucum (L.) R. Br.) is a cereal crop that is tolerant to drought, high-temperature and poor-nutrient stresses throughout its life cycle. The DOF ( DNA binding with One Finger ) family genes encode plant-specific zinc finger transcription factors. These transcription factors have a variety of functions and can be involved in regulating the stress tolerance of pearl millet. In this study, we identified 12 DOF family genes ( PgDOF s) in pearl millet. Ten of them were distributed on four chromosomes and the other two were on scaffolds (i.e., non-chromosomal sequences). Protein sequence analysis showed that PgDOFs have the DOF domain in their N-terminal regions and that other conserved motifs are also present in them. PgDOFs and DOF proteins from five other plant species were divided into seven groups, and the 12 PgDOFs could be classified into six of those seven groups. In gene expression analysis, most PgDOF s were upregulated by cold, heat, dehydration and salinity stress. These data can be useful for further characterization of the PgDOF s.

Imazethapyr-Resistant Jungle Rice (Echinochloa colona) in Soybean Growing Belt of Central India: A Case Study - Subhash Chander; Dibakar Ghosh; Vikas C. Tyagi; C. R. Chethan; Deepak Pawar; Yogita Gharde; Bhumesh Kumar; P. K. Singh (Agricultural Research, 2023)

A compendium of the best-preserved terrestrial hypervelocity impact crater in a basaltic terrain: The Lonar, India - Saranya R. Chandran; S. James; J. Aswathi; Devika Padmakumar; T. Sadeeda Marjan; R.B. Binoj Kumar; Anil Chavan; Subhash Bhandari; K.S. Sajinkumar (Earth-Science Reviews, 2023)

Climate plays a dominant role over land management in governing soil carbon dynamics in North Western Himalayas - Owais Ali Wani; Vikas Sharma; Shamal S. Kumar; Subhash Babu; K.R. Sharma; Sanjay Singh Rathore; Sudeep Marwaha; Nazir A. Ganai; S.R. Dar; Md Yeasin; Raghavendra Singh; Jaibir Tomar (Journal of Environmental Management, 2023)

Overexpression of flowering locus D (FLD) in Indian mustard (Brassica juncea) enhances tolerance to Alternaria brassicae and Sclerotinia sclerotiorum - Shashi Shekhar; Ruby Panwar; Subhash Chandra Prasad; Deepak Kumar; Anjana Rustagi (Plant Cell Reports, 2023)

RETRACTED: Rice straw derived graphene-silica based nanocomposite and its application in improved co-fermentative microbial enzyme production and functional stability - Mohammed Asiri; Neha Srivastava; Rajeev Singh; Amer Al Ali; Subhash C. Tripathi; Abdulaziz Alqahtani; Mohd Saeed; Manish Srivastava; Ashutosh Kumar Rai; Vijai Kumar Gupta (Science of The Total Environment, 2023)

Bioactive compounds from high altitude lake Arthrospira platensis HANL01: Antioxidant property, thermal stability and antibacterial assessment against multiple antibiotics resistant bacteria - Ritu Chauhan; Ashutosh Tripathi; Abhishek Chauhan; Rupesh Kumar Basniwal; Anuj Ranjan; Arpna Kumari; Vishnu D. Rajput; Evgeniya V. Prazdnova; Tatiana Minkina; Subhash C. Chauhan; Tanu Jindal; Ram Prasad (Bioresource Technology Reports, 2023)

Sustainability Assessment of Rice-Wheat System Through Organic Fertilizers and Green Manuring in Sub-Tropical Humid Climate - Subhash Chander; S. C. Tripathi; Karnam Venkatesh; Neeraj Kumar; R. P. Meena; R. S. Chhokar; Nidhi Kamboj; Nitesh Kumar (International Journal of Plant Production, 2023)

Performance and protection of pre-engineered buildings subjected to blast and earthquake excitations - Muhammed Zain Kangda; Subhash Kumar Sah; Ehsan Noroozinejad Farsangi (Innovative Infrastructure Solutions, 2023)

Transcriptome analysis identifies novel gene(s) and pathways for salt stress responses in Dandi cultivar - Ashish Kumar G. Vala; Nasreen Bano; Yogita Deshmukh; Rukam Singh Tomar; C.G. Joshi; N. Subhash (Cereal Research Communications, 2023)

Biologically derived copper oxide-based nanocatalyst using Moringa oleifera leaves and its applications in hydrolytic enzymes and biohydrogen production - Neha Srivastava; Rajeev Singh; Irfan Ahmad; Mohammed Asiri; Subhash C. Tripathi; Ashutosh Kumar Rai; P.K. Mishra; Vijai Kumar Gupta (Bioresource Technology, 2023)

Development of Rice Straw-derived Biochar-Bentonite Composite and its Application for in situ Sequestration of Ammonium and Phosphate Ions in the Degraded Mine Soil - Isha Medha; Subhash Chandra; Jayanta Bhattacharya; Biswajit Samal; Kumar Raja Vanapalli (Environmental Management, 2023)

Molecular and phytomedicinal stability of long term micropropagated Malaxis acuminata: An endangered terrestrial orchid of biopharmaceutical importance - Paromik Bhattacharyya; Subhash Kumar; Lucy Lalthafamkimi; Ritesh Sharma; Dinesh Kumar; Dharam Singh; Sanjay Kumar (South African Journal of Botany, 2023)

Multi-scale processes influencing global carbon storage and land-carbon-climate nexus: A critical review - Owais Ali WANI; Shamal Shasang KUMAR; Nazir HUSSAIN; Anas Ibni Ali WANI; Subhash BABU; Parvej ALAM; Megna RASHID; Simona Mariana POPESCU; Sheikh MANSOOR (Pedosphere, 2023)

In-Silico molecular screening of natural compounds as a potential therapeutic inhibitor for Methicillin-resistant Staphylococcus aureus inhibition - Palanichamy Nandhini; Prashant Kr Gupta; Arun Kumar Mahapatra; Agneesh Pratim Das; Subhash Mohan Agarwal; Suresh Mickymaray; Abdulaziz S. Alothaim; Mariappan Rajan (Chemico-Biological Interactions, 2023)

Genetic diversity analysis of severely infesting invasive thrips, Thrips parvispinus (Karny) in chilli (Capsicum annuum L.) in India - Kerur Vishwanath Raghavendra; Kurubarahalli Bhoothanna Ramesh; Rajan Remani Rachana; Chowdanayak Mahendra; Surender Kumar Singh; Subhash Chander (Phytoparasitica, 2023)

Foliar zinc fertilization improves yield, biofortification and nutrient-use efficiency of upland rice - Akshay Kumar Yogi; Ram Swaroop Bana; Shanti D. Bamboriya; Ram L. Choudhary; Alison M. Laing; Deepak Singh; Samarth Godara; Subhash Babu; Amresh Chaudhary (Nutrient Cycling in Agroecosystems, 2023)

Assessment of diversity in anti-nutrient profile, resistant starch, minerals and carbohydrate components in different ricebean (Vigna umbellata) accessions - Paras Sharma; Giridhar Goudar; Anil Kumar Chandragiri; R. Ananthan; K. Subhash; Anitha Chauhan; T. Longvah; Mohar Singh; Rakesh Bhardwaj; Swarup Kumar Parida; Amit Kumar Singh; Gayacharan; et al. (Food Chemistry, 2023)

Nanotechnology: a contemporary therapeutic approach in combating infections from multidrug-resistant bacteria - Basanti Brar; Sumnil Marwaha; Anil Kumar Poonia; Bhupendra Koul; Subhash Kajla; Vishnu D. Rajput (Archives of Microbiology, 2023)

Assessment of genetic diversity in Tecomella undulata by using ISSR markers - Vijay Daneva; R. S. Beniwal; Subhash Kajla; Anil Kumar Poonia; Manish Kumar; Kajal (Vegetos, 2023)

Occurrence of Microplastics in Riverine Fishes Sold for Human Consumption in Chhattisgarh, India - Ankit Shukla; Anil Patyal; Sanjay Shakya; Choodamani Chandrakar; Subhash Kumar Verma; Nitin Gade (Water, Air, & Soil Pollution, 2022)

Outbreak and Management of Serpentine Leaf Miner, Liriomyza huidobrensis (Blanchard) (Diptera: Agromyzidae), on Potato (Solanum tuberosum L.) Crop in India - Priyank Hanuman Mhatre; Shivaji Hausrao Thube; Om Navik; E. P. Venkatasalam; Sanjeev Sharma; Jagadeesh Patil; S. Subhash; K. L. Divya; Santosh Watpade; Thava Prakash Pandian; M. Abas Shah; Manoj Kumar (Potato Research, 2022)

Lonar Impact Crater, India: the Best-Preserved Terrestrial Hypervelocity Impact Crater in a Basaltic Terrain as a Potential Global Geopark - Saranya R. Chandran; S. James; J. Aswathi; Devika Padmakumar; R. B. Binoj Kumar; Anil Chavan; Vivek Bhore; Krishna Kajale; Subhash Bhandari; K. S. Sajinkumar (Geoheritage, 2022)

Using diffusion of innovation framework with attitudinal factor to predict the future of mobility in the Indian market - Subhash Chander Arora; Megha Sharma; Vinod Kumar Singh (Environmental Science and Pollution Research, 2022)

Identification of Wheat Genotypes Resilient to Terminal Heat Stress Using GGE Biplot Analysis - Kiran Devi; Sulekha Chahal; Karnam Venkatesh; Surendra Singh; Subhash Chandra Tripathi; H. M. Mamrutha; Ruchika Sharma; Sonia Sheoran; Nagendra Kumar Singh; Gyanendra Singh; Gyanendra Pratap Singh; Ratan Tiwari (Journal of Soil Science and Plant Nutrition, 2022)

Modeling Global COVID-19 Dissemination Data After the Emergence of Omicron Variant Using Multipronged Approaches - Subhash Kumar Yadav; Vinit Kumar; Yusuf Akhter (Current Microbiology, 2022)

Wheat spike blast: genetic interventions for effective management - Hanif Khan; Shabir Hussain Wani; Subhash Chander Bhardwaj; Kirti Rani; Santosh Kumar Bishnoi; Gyanendra Pratap Singh (Molecular Biology Reports, 2022)

Identification and validation of suitable housekeeping genes for gene expression studies in BCR-ABL1 positive B-lineage acute lymphoblastic leukemia - Dikshat Gopal Gupta; Neelam Varma; Ashish Kumar; Shano Naseem; Man Updesh Singh Sachdeva; Parveen Bose; Jogeshwar Binota; Minakshi Gupta; Priti Sonam; Palak Rana; Pankaj Malhotra; Subhash Varma (Molecular Biology Reports, 2022)

Persistence evaluation of fluopyram + tebuconazole residues on mango and pomegranate and their risk assessment - Vandana Tripathy; Krishan Kumar Sharma; Soudamini Mohapatra; Lekha Siddamallaiah; Nagapooja Yogendraiah Matadha; Chidanand Shiveshankar Patil; Yogesh Subhash Saindane; Bhaidas Deore; Cherukuri Sreenivasa Rao; Kaushik D. Parmar; Nitesh S. Litoriya; Paresh G. Shah; et al. (Environmental Science and Pollution Research, 2022)

Nickel-mediated lead dynamics and their interactive effect on lead partitioning and phytoremediation indices in spinach - Mohan Lal Dotaniya; Jaypal Singh Pipalde; Ramesh Chandra Jain; Rajendiran Selladurai; Subhash Chandra Gupta; Madhav Das Vyas; M Vassanda Coumar; Sonalika Sahoo; Jayanta Kumar Saha; Ajay Kumar (Environmental Monitoring and Assessment, 2022)

Characterization of five new pathotypes of Puccinia triticina identified from Northeast India, Nepal, and Bangladesh - Subodh Kumar; Subhash Chander Bhardwaj; Om Prakash Gangwar; Pramod Prasad; Ranjana Chakrabarty; Prem Lal Kashyap; Hanif Khan; Siddanna Savadi; Baidya Nath Mahato; Paritosh Kumar Malaker (Australasian Plant Pathology, 2022)

Metagenomic insights into Himalayan glacial and kettle lake sediments revealed microbial community structure, function, and stress adaptation strategies - Vijay Kumar; Subhash Kumar; Dharam Singh (Extremophiles, 2022)

Use of Petroleum-Derived Spray Oils for the Management of Vector-Virus Complex in Potato - Mohd Abas Shah; Kailash Chandra Naga; Shivaramu Subhash; Sanjeev Sharma; Raj Kumar (Potato Research, 2022)

An intelligent epilepsy seizure detection system using adaptive mode decomposition of EEG signals - Gulshan Kumar; Subhash Chander; Ahmad Almadhor (Physical and Engineering Sciences in Medicine, 2022)

Roles of Nitric Oxide in Conferring Multiple Abiotic Stress Tolerance in Plants and Crosstalk with Other Plant Growth Regulators - Rajesh Kumar Singhal; Hanuman Singh Jatav; Tariq Aftab; Saurabh Pandey; Udit Nandan Mishra; Jyoti Chauhan; Subhash Chand; Indu; Debanjana Saha; Basant Kumar Dadarwal; Kailash Chandra; Mudasser Ahmed Khan; et al. (Journal of Plant Growth Regulation, 2021)

Stress and development phenotyping of Hsp101 and diverse other Hsp mutants of Arabidopsis thaliana - Lalit Dev Tiwari; Ritesh Kumar; Vijyesh Sharma; Alok Kumar Sahu; Balram Sahu; Subhash Chandra Naithani; Anil Grover (Journal of Plant Biochemistry and Biotechnology, 2021)

ESOPA: a GUI-based MATLAB platform for estimation of earthquake spectral source parameters, inelastic attenuation, high-frequency decay kappa, and fmax-model - Rohtash Kumar; Raghav Singh; Subhash Chander Gupta; Amritansh Rai; Prashant Singh; Aquib Ali; Arjun Kumar; Satya Prakash Maurya (Arabian Journal of Geosciences, 2021)

Conservational Tillage and Weed Management Practices Enhance Farmers Income and System Productivity of Rice–Wheat Cropping System in Central India - Dibakar Ghosh; C. R. Chethan; Subhash Chander; Bhumesh Kumar; R. P. Dubey; H. S. Bisen; S. K. Parey; P. K. Singh (Agricultural Research, 2021)

Dissipation kinetics and risk assessment of iprovalicarb + propineb fungicide in tomato under different agroclimates - Vandana Tripathy; Krishan Kumar Sharma; Thomas George; Chidanand Shiveshankar Patil; Yogesh Subhash Saindane; Soudamini Mohapatra; Lekha Siddamallaiah; Abdul Rashid Khan Pathan; Amit Kumar Yadav; Khushbu Sharma; Rajbir Yadav; Ruchi Gupta; et al. (Environmental Science and Pollution Research, 2021)

Lr80: A new and widely effective source of leaf rust resistance of wheat for enhancing diversity of resistance among modern cultivars - Subodh Kumar; Subhash C. Bhardwaj; Om P. Gangwar; Akanksha Sharma; Naeela Qureshi; Vikas V. Kumaran; Hanif Khan; Pramod Prasad; Hanif Miah; Gyanendra P. Singh; Kiran Sharma; Hemlata Verma; et al. (Theoretical and Applied Genetics, 2021)

Pharmacological characterization of a structurally new class of antibacterial compound, triphenyl-phosphonium conjugated diarylheptanoid: Antibacterial activity and molecular mechanism - Shweta Kumari; Sundarraj Jayakumar; Subhash C Bihani; Neena Shetake; Raji Naidu; Vijay K Kutala; Haladhar D Sarma; Gagan D Gupta; Santosh K Sandur; Vinay Kumar (Journal of Biosciences, 2020)

Application of in vitro protein solubility for selection of microalgae biomass as protein ingredient in animal and aquafeed - G. Venkata Subhash; Neera Chugh; Supriya Iyer; Ashish Waghmare; Amar S. Musale; Rajesh Nandru; Rakhi Bajpai Dixit; Mahadev S. Gaikwad; Deepthi Menon; Rakesh Thorat; G.Raja Krishna Kumar; Vinod Nagle; et al. (Journal of Applied Phycology, 2020)

Conservation of gene architecture and domains amidst sequence divergence in the hsrω lncRNA gene across the Drosophila genus: an in silico analysis - Ranjan Kumar Sahu; Eshita Mutt; Subhash Chandra Lakhotia (Journal of Genetics, 2020)

Microbes involved in arsenic mobilization and respiration: a review on isolation, identification, isolates and implications - Payal Mazumder; Subhash Kumar Sharma; Kaling Taki; Ajay S. Kalamdhad; Manish Kumar (Environmental Geochemistry and Health, 2020)

Identification and characterization of Dicer-like genes in leaf rust pathogen (Puccinia triticina) of wheat - Himanshu Dubey; Kanti Kiran; Rajdeep Jaswal; Subhash C. Bhardwaj; Tapan Kumar Mondal; Neha Jain; N. K. Singh; Arvind M. Kayastha; Tilak Raj Sharma (Functional & Integrative Genomics, 2020)

Spatial mapping and modeling of arsenic contamination of groundwater and risk assessment through geospatial interpolation technique - Merina Ghosh; Dilip Kumar Pal; Subhash Chandra Santra (Environment, Development and Sustainability, 2020)

Influence of land configuration and organic sources of nutrient supply on productivity and quality of ginger (Zingiber officinale Rosc.) grown in Eastern Himalayas, India - Anup Das; Jayanta Layek; Subhash Babu; Manoj Kumar; Gulab Singh Yadav; Dharmendra Prasad Patel; Ramkrushna Gandhiji Idapuganti; Rattan Lal; Juri Buragohain (Environmental Sustainability, 2020)

Comparative study of coal rocks compressive behaviors and failure criteria - Harinandan Kumar; Upendra Singh Yadav; Subhash Kumar; Kishan Kumar; Ravi Yadav; Anveshika Shanker; Anurag Tripathi; Gitiksha Khandelwal (Arabian Journal of Geosciences, 2019)

Characterization of three new Yr9-virulences and identification of sources of resistance among recently developed Indian bread wheat germplasm - Om Prakash Gangwar; Subodh Kumar; Subhash Chander Bhardwaj; Prem Lal Kashyap; Pramod Prasad; Hanif Khan (Journal of Plant Pathology, 2019)

Foliar Application of Iron Fortified Bacteriosiderophore Improves Growth and Grain Fe Concentration in Wheat and Soybean - Sandeep Sharma; Subhash Chandra; Arun Kumar; Prem Bindraban; Anil Kumar Saxena; Veena Pande; Renu Pandey (Indian Journal of Microbiology, 2019)

Virulence and molecular analysis of atypical pathotypes of yellow rust pathogen in India - Om Prakash Gangwar; Subodh Kumar; Prem Lal Kashyap; Subhash Chander Bhardwaj; Pramod Prasad; Siddanna Savadi; Hanif Khan; Deepshikha (Indian Phytopathology, 2019)

Stage-specific reprogramming of defense responsive genes during Lr24-mediated leaf rust resistance in wheat - Pramod Prasad; Siddanna Savadi; Subhash Chander Bhardwaj; Prem Lal Kashyap; Om Prakash Gangwar; Hanif Khan; Subodh Kumar; Ravinder Kumar; Virupaksh Patil (Journal of Plant Pathology, 2019)

Discovery and profiling of small RNAs from Puccinia triticina by deep sequencing and identification of their potential targets in wheat - Himanshu Dubey; Kanti Kiran; Rajdeep Jaswal; Priyanka Jain; Arvind M Kayastha; Subhash C Bhardwaj; Tapan Kumar Mondal; Tilak Raj Sharma (Functional & Integrative Genomics, 2019)

Impact of dust storm on phytoplankton bloom over the Arabian Sea: a case study during March 2012 - Kunal Bali; Amit Kumar Mishra; Sachchidanand Singh; Subhash Chandra; Yoav Lehahn (Environmental Science and Pollution Research, 2019)

Foliar application of organic and inorganic iron formulation induces differential detoxification response to improve growth and biofortification in soybean - Sandeep Sharma; Hina Malhotra; Priyanka Borah; Mukesh Kumar Meena; Prem Bindraban; Subhash Chandra; Veena Pande; Renu Pandey (Plant Physiology Reports, 2019)

Azadiradione Restores Protein Quality Control and Ameliorates the Disease Pathogenesis in a Mouse Model of Huntington’s Disease - Brijesh Kumar Singh; Naman Vatsa; Vinod K. Nelson; Vipendra Kumar; Shashi Shekhar Kumar; Subhash C. Mandal; Mahadeb Pal; Nihar Ranjan Jana (Molecular Neurobiology, 2018)

Association of Peri-partum Blood Energy Metabolites with Post-partum Puerperal Metritis in Crossbred Cows - Tapas Kumar Patbandha; Tushar Kumar Mohanty; Siddhartha Shankar Layek; Arumugam Kumaresan; Kumaresh Behera; Subhash Chand (Proceedings of the National Academy of Sciences, India Section B: Biological Sciences, 2018)

What signals do herbivore-induced plant volatiles provide conspecific herbivores? - Subhash Shivaramu; Pagadala Damodaram Kamala Jayanthi; Vivek Kempraj; Raghavendra Anjinappa; Bakthavatsalam Nandagopal; Akshay Kumar Chakravarty (Arthropod-Plant Interactions, 2017)

Salivary miR-16, miR-191 and miR-223: intuitive indicators of dominant ovarian follicles in buffaloes - Prashant Singh; Naresh Golla; Pankaj Singh; Vijay Simha Baddela; Subhash Chand; Rubina Kumari Baithalu; Dheer Singh; Suneel Kumar Onteru (Molecular Genetics and Genomics, 2017)

Active oxygen species metabolism in neem (Azadirachta indica) seeds exposed to natural ageing and controlled deterioration - Alok Kumar Sahu; Balram Sahu; Avinash Soni; Subhash Chandra Naithani (Acta Physiologiae Plantarum, 2017)

Mechanical Properties of High Entropy Alloy Al0.1CoCrFeNi for Peripheral Vascular Stent Application - Karthik Alagarsamy; Aleksandra Fortier; Mageshwari Komarasamy; Nilesh Kumar; Atif Mohammad; Subhash Banerjee; Hai-Chao Han; Rajiv S. Mishra (Cardiovascular Engineering and Technology, 2016)

Effect of Sowing Date and Cultivars on Aphid Infestation in Wheat with Climate Change Adaptation Perspective - Subhash Chander; Mazhar Husain; Vishwa Pal; Himanshu Pathak; S. D. Singh; Ramesh Harit; Vinod Kumar (Proceedings of the National Academy of Sciences, India Section B: Biological Sciences, 2016)

Dose-dependent response of Trichoderma harzianum in improving drought tolerance in rice genotypes - Veena Pandey; Mohammad W. Ansari; Suresh Tula; Sandep Yadav; Ranjan K. Sahoo; Nandini Shukla; Gurdeep Bains; Shail Badal; Subhash Chandra; A. K. Gaur; Atul Kumar; Alok Shukla; et al. (Planta, 2016)

In vitro regeneration and optimization of factors affecting Agrobacterium mediated transformation in Artemisia Pallens, an important medicinal plant - Anshu Alok; Vishnu Shukla; Zarna Pala; Jitesh Kumar; Subhash Kudale; Neetin Desai (Physiology and Molecular Biology of Plants, 2016)

Erratum to: Summer monsoon rainfall trends in the Indian Himalayan region - Sandipan Mukherjee; Rajesh Joshi; Ram C. Prasad; Subhash C. R. Vishvakarma; Kireet Kumar (Theoretical and Applied Climatology, 2015)

Summer monsoon rainfall trends in the Indian Himalayan region - Sandipan Mukherjee; Rajesh Joshi; Ram C. Prasad; Subhash C. R. Vishvakarma; Kireet Kumar (Theoretical and Applied Climatology, 2015)

Comparative assessment of genetic diversity among Indian bamboo genotypes using RAPD and ISSR markers - Parth Desai; Bhavesh Gajera; Mounil Mankad; Shikha Shah; Armi Patel; Ghanshyam Patil; Subhash Narayanan; Nitish Kumar (Molecular Biology Reports, 2015)

Effect of azimuthal coverage of an earthquake on moment tensor solutions estimated by waveform inversion - Rohtash Kumar; Subhash Chander Gupta; Arjun Kumar (Arabian Journal of Geosciences, 2015)

Detection of mosaic virus disease in cassava plants by sunlight-induced fluorescence imaging: a pilot study for proximal sensing - Sadasivan Nair Raji; Narayanan Subhash; Velumani Ravi; Raju Saravanan; Changatharayil N. Mohanan; Sukumar Nita; Thangaraj Makesh Kumar (International Journal of Remote Sensing, 2015)

Population structure and association mapping studies for important agronomic traits in soybean - BHUPENDER KUMAR; AKSHAY TALUKDAR; INDU BALA; KHUSHBU VERMA; SANJAY KUMAR LAL; RAMESH LAL SAPRA; B. NAMITA; SUBHASH CHANDER; RESHU TIWARI (Journal of Genetics, 2014)

In vitro and in vivo pathogenicity studies of Pasteurella multocida strains harbouring different ompA - Shailja Katoch; Mandeep Sharma; R. D. Patil; Sandeep Kumar; Subhash Verma (Veterinary Research Communications, 2014)

Efficiency of ISSR and RAPD markers in genetic divergence analysis and conservation management of Justicia adhatoda L., a medicinal plant - Amit Kumar; Priyanka Mishra; Subhash Chandra Singh; Velusamy Sundaresan (Plant Systematics and Evolution, 2014)

Reversal of boswellic acid analog BA145 induced caspase dependent apoptosis by PI3K inhibitor LY294002 and MEK inhibitor PD98059 - Anup S. Pathania; Amit Joshi; Suresh Kumar; Santosh K. Guru; Shashi Bhushan; Parduman R. Sharma; Wajid W. Bhat; Ajit K. Saxena; Jaswant Singh; Bhahwal A. Shah; Samar S. Andotra; Subhash C. Taneja; et al. (Apoptosis, 2013)

Profiling of virulence associated genes of Pasteurella multocida isolated from cattle - Subhash Verma; Mandeep Sharma; Shailja Katoch; Lovit Verma; Sandeep Kumar; Vishal Dogra; Rajesh Chahota; Prasenjit Dhar; Geetanjali Singh (Veterinary Research Communications, 2013)

A Simple and Efficient In Vitro Mass Multiplication Procedure for Stevia rebaudiana Bertoni and Analysis of Genetic Fidelity of In Vitro Raised Plants Through RAPD - Arpan R. Modi; Ghanshyam Patil; Nitish Kumar; Amritpal S. Singh; N. Subhash (Sugar Tech, 2012)

Assessment of genetic fidelity of micropropagated date palm (Phoenix dactylifera L.) plants by RAPD and ISSR markers assay - Nitish Kumar; Arpan R. Modi; Amritpal S. Singh; Bhavesh B. Gajera; Armi R. Patel; Mukesh P. Patel; Naraynan Subhash (Physiology and Molecular Biology of Plants, 2010)

Effect of Novel Amino Acids and Dipeptides Substituted 3-Morpholino Arecoline Derivatives as Muscarinic Receptor 1 Agonists in Alzheimer’s Dementia Models - S. R. Ranganatha; Manish Malviya; Y. C. Sunil Kumar; K. Vinaya; D. S. Prasanna; M. N. Subhash; K. S. Rangappa (International Journal of Peptide Research and Therapeutics, 2009)

Agrobacterium-mediated genetic transformation of pineapple var. Queen using a novel encapsulation-based antibiotic selection technique - Gaurab Gangopadhyay; Subhash Kanti Roy; Sangita Basu Gangopadhyay; Kalyan Kumar Mukherjee (Plant Cell, Tissue and Organ Culture (PCTOC), 2009)

Sex determination in 6 bovid species by duplex PCR - Prashant; Digpal S. Gour; Prem P. Dubey; Anubhav Jain; Subhash C. Gupta; Balwinder K. Joshi; Dinesh Kumar (Journal of Applied Genetics, 2008)

ATRA promotes alpha tocopherol succinate-induced apoptosis in freshly isolated leukemic cells from chronic myeloid leukemic patients - Surender Kumar; Krishan Lal Khanduja; Neelam Verma; Subhash C. Verma; Pramod Kumar Avti; Chander Mohan Pathak (Molecular and Cellular Biochemistry, 2007)

A triterpenediol from Boswellia serrata induces apoptosis through both the intrinsic and extrinsic apoptotic pathways in human leukemia HL-60 cells - Shashi Bhushan; Ajay Kumar; Fayaz Malik; Samar Singh Andotra; Vijay Kumar Sethi; Indu Pal Kaur; Subhash Chandra Taneja; Ghulam Nabi Qazi; Jaswant Singh (Apoptosis, 2007)

High-frequencyin vitro flowering in six species ofceropegia - Aneesh Kumar Nair; Naik Dhiraj Dilip; Pandit Sagar Subhash (Journal of Plant Biology, 2007)

Residue Evaluation of Controlled-Release Formulations of Imidacloprid Against Rice Leaf Folder - B. Ram Prasad; Vidya S. Singh; Subhash Chander; Jitendra Kumar (Bulletin of Environmental Contamination and Toxicology, 2007)

Inhibition of Biosynthesis and Activity of Nitrogenase in Azospirillum brasilense Sp7 Under Salinity Stress - Anil Kumar Tripathi; Thirunavukkarasu Nagarajan; Subhash Chandra Verma; Daniel Le Rudulier (Current Microbiology, 2002)

Contributory presentations/posters - N. Manoj; V. R. Srinivas; A. Surolia; M. Vijayan; K. Suguna; R. Ravishankar; K. Suguna; A. Surolia; M. Vijayan; R. Schwarzenbacher; K. Zeth; Diederichs; et al. (Journal of Biosciences, 1999)